Quality of colonoscopy in an organised colorectal cancer screening programme with immunochemical faecal occult blood test: the EQuIPE study (Evaluating Quality Indicators of the Performance of Endoscopy). Issue 9 (16th September 2014) - Zorzi, Manuel; Senore, Carlo; Da Re, Filippo; Barca, Alessandra; Bonelli, Luigina Ada; Cannizzaro, Renato; Fasoli, Renato; Di Furia, Lucia; Di Giulio, Emilio; Mantellini, Paola; Naldoni, Carlo; Sassatelli, Romano; et al.
Abstract : Objectives: To assess variation in the main colonoscopy quality indicators in organised colorectal cancer (CRC) screening programmes based on faecal immunochemical test (FIT). Design: Data from a case-series of colonoscopies of FIT-positive subjects were provided by 44 Italian CRC screening programmes. Data on screening history, endoscopic procedure and histology results, and additional information on the endoscopy centre and the endoscopists were collected. The adenoma detection rate (ADR) and caecal intubation rate (CIR) were assessed for the whole population and the individual endoscopists. To explore variation in the quality indicators, multilevel analyses were performed according to patient/centre/endoscopist characteristics. Results: We analysed 75 569 (mean age: 61.3 years; men: 57%) colonoscopies for positive FIT performed by 479 endoscopists in 79 centres. ADR ranged from 13.5% to 75% among endoscopists (mean: 44.8%). ADR was associated with gastroenterology specialty (OR: 0.87 for others, 95% CI 0.76 to 0.96) and, at the endoscopy centre level, with the routine use of sedation (OR: 0.80 if occasional (<33%); 95% CI 0.64 to 1.00) and availability of screening-dedicated sessions (OR: 1.35; 95% CI 1.11 to 1.66). CIR ranged between 58.8% and 100% (mean: 93.1%). Independent predictors of CIR at the endoscopist level were the yearly number of screening colonoscopies performed (OR: 1.51 for endoscopists with >600 colonoscopies; 95% CI 1.11 to 2.04) and, at the endoscopy centre level, screening-dedicated sessions (OR: 2.18; 95% CI 1.24 to 3.83) and higher rates of sedation (OR: 0.47 if occasional; 95% CI 0.24 to 0.92). Conclusions: The quality of colonoscopy was affected by patient-related, endoscopist-related and centre-related characteristics. Policies addressing organisational issues should improve the quality of colonoscopy in our programme and similar programmes.